Possible Immunosuppressive Effects of Drug Exposure and Environmental and Nutritional Effects on Infection and Vaccination - H. P. Huemer (Mediators of Inflammation)
A variety of drugs which are not primarily considered to be immunosuppressive agents have been described to modulate the humoral and cellular immune response in humans or animals. Thereby they may have an influence on the effectiveness and possible side effects of vaccines. This mini review lists some of the different substance classes and also some of endogeneous, infectious, nutritional, and environmental influences with suspected capability to interfere with immunizations. Studies in most cases focused on substances with known immunosuppressive functions, but there is growing evidence for immunomodulatory effects also of commonly used drugs with wide distribution. In particular combinations of those antiproliferative and antiphlogistic side effects of different substance classes have not been studied in detail but may substantially interfere with the development of a functional humoral and cellular immune response. The drugs of importance include antipyretics, anticoagulants, tranquilizers, and substances influencing lipid metabolism but also commonly used drugs of abuse like alcohol or cannabinoids. Additional substances of environmental, nutritional, or microbiological origin may also play a role but their combinatory/synergistic effects have been disregarded so far due to the lack of systematic data and the complex study designs necessary to elucidate those complex epidemiologic questions.